2016
DOI: 10.1002/chem.201604561
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Procedure for the Synthesis of 1,5‐Benzodiazepines from N‐Allyl‐2‐bromoanilines

Abstract: A new one-pot procedure that includes an initial titanium-catalyzed intermolecular hydroaminoalkylation of N-allyl-2-bromoanilines with N-methylanilines and a subsequent intramolecular Buchwald-Hartwig amination directly gives access to pharmacologically relevant 1,5-benzodiazepines. The process takes advantage of the excellent regioselectivity of the initial hydroaminoalkylation performed in the presence of a titanium mono(formamidinate) catalyst and the fact that the exclusively formed branched hydroaminoalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Because overall the best result of the intramolecular Buchwald-Hartwig amination of 22 waso btained with RuPhos, this ligand was then used for the finally planned development of ao ne-pot procedure for the synthesis of 1,5-benzoazasilepines from allyl(2-bromophenyl)silanes ( Table 5). [7] However, the sensitivity of the titanium catalyst against alcohols and carbonyl compounds rules out the possibility to develop ar elated one-pot protocol in which both the titaniuma nd the palladium catalysta re added to the flask at the same time. [7] However, the sensitivity of the titanium catalyst against alcohols and carbonyl compounds rules out the possibility to develop ar elated one-pot protocol in which both the titaniuma nd the palladium catalysta re added to the flask at the same time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because overall the best result of the intramolecular Buchwald-Hartwig amination of 22 waso btained with RuPhos, this ligand was then used for the finally planned development of ao ne-pot procedure for the synthesis of 1,5-benzoazasilepines from allyl(2-bromophenyl)silanes ( Table 5). [7] However, the sensitivity of the titanium catalyst against alcohols and carbonyl compounds rules out the possibility to develop ar elated one-pot protocol in which both the titaniuma nd the palladium catalysta re added to the flask at the same time. [7] However, the sensitivity of the titanium catalyst against alcohols and carbonyl compounds rules out the possibility to develop ar elated one-pot protocol in which both the titaniuma nd the palladium catalysta re added to the flask at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…For that purpose, ah ydroaminoalkylation reaction mixture of allylsilane 21 and N-methylaniline (1)i nt oluene was initially heatedt o1 40 8Cf or 24 hi nt he presence of 10 mol %o fc atalyst IV.A fterwards, 2.5 mol %P d 2 (dba) 3 ,7mol %R uPhos, sodium tert-butoxide and additional toluene were added and the resulting reactionm ixture was heatedt o1 10 8Cf or additional 24 h. The yield of 83 % in which 1,5-benzoazasilepine 23 was obtained after chromatographic purification ( Table 5, entry 1) again underlines the wellestablished fact that the Buchwald-Hartwig amination tolerates the presence of the reagents used in hydroaminoalkyla-tion reactions. [7] However, the sensitivity of the titanium catalyst against alcohols and carbonyl compounds rules out the possibility to develop ar elated one-pot protocol in which both the titaniuma nd the palladium catalysta re added to the flask at the same time. To finally investigate the scope of the onepot procedure, we then reacteda dditional ortho-, meta-, and para-substituted N-methylanilines with allylsilane 21.A se xpecteda nd in good agreement with the results obtained for the hydroaminoalkylation of simple allylsilanes presented in Ta ble 2, it was found that para-o rmeta-substituted N-methylanilinesu ndergo smooth reactiont og ive the desired 1,5-benzoazasilepines in good yields between 66 and 84 %( Ta ble 5, entries [3][4][5][6][7][8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations